Organ Transplantation in Saudi Arabia: Psychological Evaluation and Sharia-Legal Framework - Hajed A. Alotaibi; Motaz T. Alotaibi (PT. Islamic Research Publiser, 2026)
The case of organ donation and transplantation in Saudi Arabia presents complex ethical issues concerning the protection of donors, patient welfare, and societal trust within an Islamic ethical system that emphasises the right to life, non-maleficence, and amānah. The Saudi Centre of Organ Transplantation (SCOT) coordinates governance in this area, while clinical evidence indicates that psychosocial factors—including coercion risk, mental health status, and family dynamics—significantly influence donor and recipient outcomes. This paper employs a doctrinal–normative–evidence synthesis drawing on official Saudi donor policies, Islamic jurisprudential foundations of necessity, harm prevention, and consent protection, as well as existing clinical literature on psychosocial considerations in both living and deceased donor contexts. The findings support a Saudi-proportional model of protective safeguarding, in which organ donation is deemed morally defensible when it is freely given, medically safe, and minimises harm through structured psychosocial screening, independent donor advocacy, and systematic follow-up. This Sharia–legal–psychological continuum strengthens vulnerability assessment, enhances donor protection, improves patient welfare, facilitates culturally sensitive family engagement without undermining donor autonomy, and aligns data governance with Saudi Arabia's digital transformation agenda. Other Muslim-majority jurisdictions may adopt this framework to develop comparable models that integrate Islamic ethics with contemporary transplantation regulatory standards. Academically, this paper contributes by proposing the first operationalised